Problem-driven iterative approaches and wider governance reform - Rao, Sumedh (GSDRC, University of Birmingham, 2014)
Identify evidence which suggests that problem-driven, iterative approa ches to public sector reform can deliver more substantial, wider, long -term governance reform.